Caracterización del mucílago de caco (Theobroma Cacao L.) nacional y trinitario en el cantón Quevedo - Moreira Morán, Stefany Tamara (2019)
This research was carried out in the Bromatology Laboratory of the Faculty of Animal Sciences, located in the Experimental Estate "La María" of the State Technical University of Quevedo. It was aimed at characterizing an agricultural waste such as the cocoa mucilage of 2 varieties widely used in the environment which are Trinitarian cocoa and national cocoa, thus giving added value and knowing the qualities of this product. A Bifactorial Completely Random Design (DCA) with 6 treatments and 4 repetitions was used. Determining as Factor A, the type of Cocoa Mucílago and Factor B The Collection Zone that were Zone 1 (The Dam), Zone 2 (INIAP) and Zone 3 (Farm “4 Brothers”). For the comparison of means, the Tukey test (p≤ 0.05) was used. The variables studied were Physical-Chemical and Nutritional Analysis: Acidity, pH, ° Brix, Humidity, Ash, Protein. Fat, Fiber, Vitamin C, reporting that if there was a significant difference between treatments except for Humidity and Ash that no significant difference was found. Regarding the microbiological analysis applied to the cocoa mucilage, it was recorded that there is no presence of total aerobes. Once the organoleptic analyzes were carried out, it was proved that T3 (Trinitarian cocoa mucilage - Zone 3 “Finca 4 Hermanos”) was the treatment that had the highest degree of acceptability on the part of the tasters, due to its sweet taste and its cocoa smell. Keywords: Cocoa Mucilage, National, Trinitarian, Organoleptic.